Itching in skin allergic diseases: dermocosmetics between diagnostic work-up and innovative or emerging drugs. Review on proper advice and prescription - Di Muzio, Gioia; Bonfranceschi, Andrea; Santini, Stefania; Scesa, Carla; Bartoletti, Emanuele (Aesthetic Medicine, 2025)
Introduction: Itch or pruritus is “an unpleasant sensation that evokes the desire to scratch”; it is defined as “chronic” if it persists for more than six weeks. Many authors include chronic itching among allergic-immunological disorders. Chronic spontaneous urticaria, atopic dermatitis, allergic contact dermatitis, and prurigo nodularis are some of the allergic diseases characterized by itch. This symptom, as well as being histaminergic, can be supported by specific sensory neuronal circuits and by inflammatory mediators, epithelial and effector cytokines, and other molecules which, through distinct, interdependent or synergistic pathways, are involved in chronic itching.Objectives: This work aims to provide an updated consultation and review of the literature regarding pruritus, in both diagnostic and therapeutic contexts. It also aims to evaluate the role of topical and active cosmetic ingredients in soothing itch and repairing the barrier damage responsible for it.Methods: A review of available literature (PubMed, various search terms) was conducted. Indications and guidelines were analyzed regarding topical ingredients considered effective in addressing itch and skin barrier repair.Results: A diagnostic-therapeutic algorithm is proposed, based on recent findings on the biology of pruritus and targeted therapies. The rationale for a dermocosmetic prescription is identified as an alternative, complementary, or synergistic therapeutic option alongside traditional or innovative drugs.Conclusions: Recent insights into the biology of pruritus, a debilitating symptom in many allergic diseases, have led to the development of precise diagnostic-therapeutic algorithms. While new molecules and targeted drugs are being explored, hydrating topicals have been shown to alleviate symptoms, improve skin barrier function, and reduce allergen penetration and bacterial contamination.